Herpes simplex virus infection generates large tandemly reiterated simian virus 40 DNA molecules in a transformed hamster cell line. - Matz, B (1987)
When the simian virus 40 (SV40)-transformed Syrian hamster cell line Elona is infected with herpes simplex virus type 1, an excessive amplification of SV40-specific DNA sequences occurs. Analysis of total DNA from herpes simplex virus-infected cells revealed that amplified DNA sequences were present predominantly in a high-molecular-weight form, consisting of a tandem array of many unit-length SV40 DNA molecules. Repeat units of amplified DNA were found to be very similar to standard SV40 DNA as was shown by restriction analyses, except for a small deletion close to the origin of replication, which could also be detected in the chromosomal DNA of uninfected cells. A procedure, devised for selective enrichment of amplified SV40 DNA molecules from the bulk of cellular and herpesviral DNA, allowed molecular cloning of single repeat units and nucleotide sequence analysis of the relative genomic region.